Classification of functionality of people with diabetic peripheral neuropathy based on international classification of functioning, disability and health Core set (ICF-CS) of diabetes mellitus - Fatma, Sobia; Noohu, Majumi M. (Journal of diabetes and metabolic disorders, 2020)
Purpose The aim of this study was the application of International Classification of Functioning, Disability and Health Core Set (ICF- CS) of Diabetes Mellitus (DM) to investigate body function impairment (BF) & body structure (BS), activity limitation & participation restriction in people with diabetes mellitus with and without peripheral neuropathy. Method A total of 120 subjects with diabetes were interviewed using four categories of the ICF-CS of DM through ICF documentation form including body functions, body structures, activities and participation, and environmental factors. Results Subjects with diabetic peripheral neuropathy (DPN) experienced more physical dysfunctions and impairments when compared with subjects having diabetes without peripheral neuropathy when assessed with ICF-CS of DM. DPN patients experienced significant problem in 19 categories in BF, 3 categories in BS, 10 categories in activity and participation and 4 categories in environmental factors when compared with diabetes patients without peripheral neuropathy on chi square analysis. Findings of regression analysis suggest that people with DPN have more chances of impairments in BF and BS, activities and participation, and environmental factors. Conclusion The difference observed between subjects having diabetes with and without peripheral neuropathy on the scores of ICF-CS domains suggest that, people with DPN faces more problems in health and function. These people should be targeted with more intensive care for improving the health standards.